2020
DOI: 10.1101/2020.03.14.20036178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correcting under-reported COVID-19 case numbers: estimating the true scale of the pandemic

Abstract: The COVID-19 virus has spread worldwide in a matter of a few months, while healthcare systems struggle to monitor and report current cases. Testing results have struggled with the relative capabilities, testing policies and preparedness of each affected country, making their comparison a non-trivial task. Since severe cases, which more likely lead to fatal outcomes, are detected at a higher rate than mild cases, the reported virus mortality is likely inflated in most countries. Lockdowns and changes in human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 11 publications
4
93
0
5
Order By: Relevance
“…At the other end of the testing spectrum, we estimate that for each infected individual tested in Germany, between 0.2 and 2 individuals might have not been tested at the beginning of the epidemic. A higher testing rate for Germany is in qualitative agreement with estimates given elsewhere 22,26 . Our estimates for the reporting rate, however, tend to be higher than those obtained by Jagodnik et al 26 and the differences we found between countries are not as extreme as those given by Chicci et al 22 Assuming that the testing rate remains constant during the course of epidemics and no control interventions are implemented, our model predicts that the number of tested and untested infected individuals would evolve in parallel in all the studied outbreaks which would last for around 12 weeks in all cases (see Figure 3).…”
Section: Model Calibration Under-reporting and Reporting Delayssupporting
confidence: 91%
See 2 more Smart Citations
“…At the other end of the testing spectrum, we estimate that for each infected individual tested in Germany, between 0.2 and 2 individuals might have not been tested at the beginning of the epidemic. A higher testing rate for Germany is in qualitative agreement with estimates given elsewhere 22,26 . Our estimates for the reporting rate, however, tend to be higher than those obtained by Jagodnik et al 26 and the differences we found between countries are not as extreme as those given by Chicci et al 22 Assuming that the testing rate remains constant during the course of epidemics and no control interventions are implemented, our model predicts that the number of tested and untested infected individuals would evolve in parallel in all the studied outbreaks which would last for around 12 weeks in all cases (see Figure 3).…”
Section: Model Calibration Under-reporting and Reporting Delayssupporting
confidence: 91%
“…A higher testing rate for Germany is in qualitative agreement with estimates given elsewhere 22,26 . Our estimates for the reporting rate, however, tend to be higher than those obtained by Jagodnik et al 26 and the differences we found between countries are not as extreme as those given by Chicci et al 22 Assuming that the testing rate remains constant during the course of epidemics and no control interventions are implemented, our model predicts that the number of tested and untested infected individuals would evolve in parallel in all the studied outbreaks which would last for around 12 weeks in all cases (see Figure 3). We see, however, that the epidemic in Germany would belong to a different class in the sense that the number of untested infected individuals remains smaller than the number of tested individuals during the whole epidemic.…”
Section: Model Calibration Under-reporting and Reporting Delayssupporting
confidence: 91%
See 1 more Smart Citation
“…These data should be taken with caution because they can be strongly influenced by the number of effectuated tests. According to some media reports, there is a shortage of testing facility and/or shortage of testing kits in many countries, and the accurate number of infected individuals can be much larger [7]. Dynamics of the number of infected individuals can be influenced by various factors, in particular, by their spatial distribution and nature of social mixing.…”
Section: -1000 1000-10000mentioning
confidence: 99%
“…Multiple studies have shown that the reported numbers of confirmed cases may underestimate the true number of cases by a factor of 10 or even more. [4][5][6] While such studies can provide useful insights, they often cannot explain the observed change in the CFR during an epidemic.…”
Section: Introductionmentioning
confidence: 99%